2014
DOI: 10.1097/wnn.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study of Differences in Brain Activity Among Elite, Expert, and Novice Archers at the Moment of Optimal Aiming

Abstract: The more localized neural activity of elite and expert archers than novices permits greater efficiency in the complex processes subserved by these regions. The elite group's high activity in the cerebellar dentate indicates that the cerebellum is involved in automating simultaneous movements by integrating the sensorimotor memory enabled by greater expertise in self-paced aiming tasks. A companion article comments on and generalizes our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 0 publications
3
45
0
1
Order By: Relevance
“…Importantly, functional connectivity is related to motor skill learning (Albert et al, 2009;Song, Gotts, Dayan, & Cohen, 2015) and to higher levels of motor skill (Di, Zhu, Jin, Wang, Ye, Zhou et al, 2012;Ito, Matsuda, & Shimojo, 2015;Kim, Han, Kim, & Han, 2015;Milton, Solodkin, Hluštík, & Small, 2007;Li, He, Huang, Zhang, Lu, Lai et al, 2015). Functional connectivity tracks the learning of motor skills, and more distinct functional connections are associated with higher skill (Kim, Chang, Kim, Seo, Ryu, Lee et al, 2014;Milton et al, 2007).…”
Section: Mechanisms For Attentional Focus Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, functional connectivity is related to motor skill learning (Albert et al, 2009;Song, Gotts, Dayan, & Cohen, 2015) and to higher levels of motor skill (Di, Zhu, Jin, Wang, Ye, Zhou et al, 2012;Ito, Matsuda, & Shimojo, 2015;Kim, Han, Kim, & Han, 2015;Milton, Solodkin, Hluštík, & Small, 2007;Li, He, Huang, Zhang, Lu, Lai et al, 2015). Functional connectivity tracks the learning of motor skills, and more distinct functional connections are associated with higher skill (Kim, Chang, Kim, Seo, Ryu, Lee et al, 2014;Milton et al, 2007).…”
Section: Mechanisms For Attentional Focus Effectsmentioning
confidence: 99%
“…Effective structural connections within brain regions would appear to lay the groundwork for the establishment of efficient functional connections across brain networks. Such connectivity appears to be a hallmark of experienced and expert performers (Di et al, 2012;Ito et al, 2015;Kim et al, 2015;Kim et al, 2014;Li et al, 2015;Milton et al, 2007).…”
Section: Conclusion and Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, neural correlates of performance in archers (Kim et al, 2014), altered insula activation in expert meditators (Lutz et al, 2013), distinct patterns of olfactory regions and hippocampus activation in perfumers when imaging smell (Plailly et al, 2012) and, during wine tasting, a functional magnetic resonance imaging (fMRI) study showed that wine experts (sommeliers) showed increased activation of the memory network (Pazart et al, 2014).…”
mentioning
confidence: 99%
“…There is evidence that during the aiming phase, neural activity differentiates performance by skill level. Kim et al (2014) investigated brain activity in elite, expert and novice archers during a simulated archery aiming task by means of functional magnetic resonance imaging (fMRI). They found more localized neural activity for elite and expert archers when compared to novices, permitting greater efficiency of the complex processes by these regions.…”
Section: Introductionmentioning
confidence: 99%